Laser tongue base mucosectomy is a useful diagnostic tool in the management of unknown primary cancers of the head and neck region. Issue 4 (8th June 2022) - Olaleye, O; Nassif, R; Fleming, B; Burrows, S
Abstract: Objective: Tongue base mucosectomy identified cancer in 78 per cent of cancers of unknown primary in a recent meta-analysis. The carbon dioxide laser is an alternative technique if there is no access to a robot. This study aimed to describe the steps for undertaking tongue base mucosectomy using the carbon dioxide laser and its diagnostic utility in cancers of unknown primary. Method: This was a prospective feasibility study utilising carbon dioxide laser for tongue base mucosectomy in cancers of unknown primary. Data collected included demographic data and p16 status. Results: There were 14 cancers of unknown primary with 86 per cent p16 positivity on immunohistochemistry. Laser tongue base mucosectomy alone identified the cancer primary in 7 of 12 (58 per cent) cancers of unknown primary among p16 positive tumours and 0 of 2 (0 per cent) among p16 negative tumours. Combining bilateral tonsillectomy with laser tongue base mucosectomy resulted in identification of the primary cancer in 8 of 12 (67 per cent) p16 positive tumours. Conclusion: In centres without a robot, tongue base mucosectomy using the carbon dioxide laser is a viable alternative, especially in combination with bilateral tonsillectomy in p16 positive cases.